Development of a prototype of multi-agent system of network interaction of educational institutions - Yu. F. Telnov; A. V. Danilov; R. I. Diveev; V. A. Kazakov; E. V. Yaroshenko (Открытое образование (Москва), 2019)
The aim of the research is to develop a prototype of the intelligent multi-agent system for dynamic interaction of the intelligent agents in the integrated information and educational space to solve the problem of formation of joint educational programs by several educational institutions. Materials and methods. In modern conditions of digital transformation of education the organization of network training of students on dynamically formed educational programs in accordance with the needs of the labor market and the individual requirements of students is becoming increasingly important. It is proposed to develop a software platform based on intelligent multi-agent technology for flexible integration of educational resources and implementation of joint educational programs by several interacting educational institutions. As a basis for the development of the software prototype architecture, the specifications of the developer community for the standardization of agent technologies FIPA (the Foundation for Intelligent Physical Agents), and the software tool environment – JADE framework (Java Agent Development Network) were chosen.Results. The paper presents the architecture of intelligent multi-agent system for network interaction of educational institutions in the integrated information and educational space, which allows to dynamically forming educational programs in accordance with the requested professional competencies. The structure of the ontology of information and educational space, providing the interaction of intelligent agents, is justified, and the mechanism of its display from the OWL format to the format of the tool environment JADE, using the plugin Protege is described. The description of the software prototype, the structure of intelligent agents in the JADE format and the technology of agent interaction, based on the FIPA protocols in the process of educational programs formation is presented.Conclusion. The implementation of the multi-agent system prototype for network interaction of educational institutions allows you to quickly create educational programs in accordance with individual and group learning trajectories under the specific formed professional competence. The presented software prototype with some modification can be used for other subject areas of the digital economy, involving the dynamic formation of network structures of interaction for business partners.